PENTINGNYA PENDIDIKAN KARAKTER DALAM DUNIA PENDIDIKAN - Nabila Putri Abdhiyani; An’Nisa Nur Zahra; Ikmawati, Ikmawati; Zainuddin Untu (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
Forming children's character is very necessary not only in the school environment but also includes the home environment and social environment. This is no longer targeting children who attend early childhood education, but also targeting adults. Competition provides an overview of what will be revealed in the following years. Of course it will be a burden for us and parents today. Children must be ready to compete with their peers from various parts of the world. Even those of us who are still working in the future will feel the same way. In order to demand the quality of human resources in the next millennium era, good character is certainly very necessary. Therefore, character is the main goal of an individual.